Effects of the Herbst appliance in growing orthodontic patients with different underlying vertical patterns - Deen Emily; Woods Michael G. (Sciendo, 2015)
The present study involved an assessment of the effects of the Herbst appliance used for Class II correction in subjects with different vertical facial patterns.